2021
DOI: 10.1111/ahg.12416
|View full text |Cite
|
Sign up to set email alerts
|

Genetics background of β‐thalassemia (3.5 kb deletion) in Southern Thailand: Haplotype analysis using novel reverse dot blot hybridization

Abstract: β-thalassemia (β-thal) (3.5 kb deletion or NC_000011.10:g.5224302-5227791del3490bp) is a common mutation in southern Thailand. This study aimed to determine genetic diversity in subjects with β-thal (3.5 kb deletion) alleles and to ascertain the origin of this mutation using haplotype and phylogenetic analysis. The study was carried out on members of the southern Thai population, including 45 normal individuals, 116 heterozygous β-thal (3.5 kb deletion) and one homozygous β-thal (3.5 kb deletion). The 5′-haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, it has been reported that eight common β-thalassemia mutations in Thailand (including codon 41/42 (-TTCT), codon 17 (A > T), NT-28 (A > G), IVS II-654 (C > T), codon 19 (A > G), codon 26; HbE (G > A), IVS I-1 (G > C) and IVS I-5 (G > C)) represent more than 85% of the total β-thalassemia mutations [ 3 , 4 , 5 ]. Several previous studies have reported the genetic relationship between populations, chromosome background of the gene and linkage analysis, as well as differences in clinical phenotypic expression using haplotype and phylogenetic analyses [ 6 , 7 , 8 ]. Single nucleotide polymorphisms (SNPs) within the β-globin gene cluster on chromosome 11 have been found, with seven–eight polymorphic sites commonly studied [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that eight common β-thalassemia mutations in Thailand (including codon 41/42 (-TTCT), codon 17 (A > T), NT-28 (A > G), IVS II-654 (C > T), codon 19 (A > G), codon 26; HbE (G > A), IVS I-1 (G > C) and IVS I-5 (G > C)) represent more than 85% of the total β-thalassemia mutations [ 3 , 4 , 5 ]. Several previous studies have reported the genetic relationship between populations, chromosome background of the gene and linkage analysis, as well as differences in clinical phenotypic expression using haplotype and phylogenetic analyses [ 6 , 7 , 8 ]. Single nucleotide polymorphisms (SNPs) within the β-globin gene cluster on chromosome 11 have been found, with seven–eight polymorphic sites commonly studied [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%